Effects of Endophytic Fungal Extract on Seed Germination and Seedling Growth of Aerides houlletiana Rchb.f. (Orchidaceae) In Vitro - Suwattanachat, Natta; Posoongnoen, Saijai; Thummavongsa, Theera (Burapha Science Journal, 2026)
This research was purposed to isolate endophytic fungi from Aerides houlletiana Rchb.f. and to increase seed germination and seedling growth of this orchid by fungal. The results revealed that 19 fungal isolates were isolated and found ability to produce indoleacetic acid (IAA) content in range of 0.78-41.04 µg/mL. Three highest levels of IAA content were isolates 10, 14 and 03 respectively, and were further extracted secondary metabolites from culture broth and analyzed for the effect on seed germination and growth of the orchid. Fungal isolate 14 at 10 mg/L showed high percentages of seed germination and significant different (p < 0.05) compared with control. Growth of seedling exhibited that medium supplemented with 10 mg/L of fungal isolate 10 presented the highest leaf length and significant different compared with all treatments. Each fungal isolates were identified by sequencing the internal transcribed spacer (ITS): ITS1 and ITS4 regions. It indicated that the fungal isolate 10 was Colletotrichum gloeosporioides (100% identity). Whilst, fungal isolate 03 and 14 were Lasiodiplodia theobromae (100% identity).